2018
DOI: 10.3390/diseases6020032
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication with Antibiotics, Attitude and Knowledge of Antibiotic Resistance among Community Residents and Undergraduate Students in Northwest Nigeria

Abstract: This study set out to evaluate self-medicated antibiotics and knowledge of antibiotic resistance among undergraduate students and community members in northern Nigeria. Antibiotic consumption pattern, source of prescription, illnesses commonly treated, attitude towards antibiotics, and knowledge of antibiotic resistance were explored using a structured questionnaire. Responses were analyzed and summarized using descriptive statistics. Of the 1230 respondents from undergraduate students and community members, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 24 publications
5
50
0
3
Order By: Relevance
“…Mixed findings have been observed by many authors in this regard. [4,11,21,23,25,29] The mean score % of awareness for the fact that poor or lack of infection control measures is a cause for development of resistance was 63% in the present study. Similar level of awareness has been coated by other studies from different parts of the world.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Mixed findings have been observed by many authors in this regard. [4,11,21,23,25,29] The mean score % of awareness for the fact that poor or lack of infection control measures is a cause for development of resistance was 63% in the present study. Similar level of awareness has been coated by other studies from different parts of the world.…”
Section: Discussionmentioning
confidence: 47%
“…Many studies have reported low level of awareness among students in this regard. [4,14,2325] A high level of disagreement (84.7%) was observed among the students to the point that antibiotics are indicated to reduce pain and inflammation in the body. Similar kind of disagreement has been observed by Sakeena MHF et.al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations